Vírus da anemia infecciosa equina em asininos: sorologia em animais errantes e avaliação " In Vitro " da resposta em macrófagos - Fernanda Gonçalves de Oliveira (2016)
Equine infectious anemia virus (EIAV) is a lentivirus agent which infects all Equidae members throughout the world however the vast majority of studies have been conducted in horses (Equus caballus) with comparatively little information available for other equid species. Brazil has one of the most abundant donkey (E. asinus) populations of any nation especially in the Northeast of the country where they have been released and allowed pursue na almost feral existence with unknown sanitary status. The present study had two objectives: first, was to conduct a serological survey for EIAV in populations of free living donkeys in Mossoró city and adjacent areas, Rio Grande do Norte state, Brazil using combination of EIA diagnostic tests; second, was to evaluate the cytokine profile of equine and donkeys PBMC and, donkeys macrophages after challenge with virulent and avirulent EIAV strains in vitro. The EIA seropositive rate was 1.63% in officially approved AGID test. However, subsequent testing using CELISA and rgp90 ELISA with IB used to clarify discrepant results found between AGID and both ELISA demonstrated that the EIA rate was underestimated by 50%. A potentially highly significant finding is that 56.9% of the donkey serum samples had reactivity to EIAV p26 only in IB. At the in vitro infections, the equine PBMC showed increased expression of TNF- (24h), IL-6 e IFN- (96 h) after infection with EIAVWYO compared to donkeys PBMC. In the experiments of donkey macrophages infections with virulent and avirulent EIAV strains, it was not observed dysregulations in cytokine expression such as TNF-, IL-1, IL-6 e TGF- (p0,05). Additional studies are needed to investigate whether the donkeys that reacted with p26 only had recent exposure to EIAV strains with envelope glycoproteins that are different from any other that have been previously characterized or other retrovirus not yet described. In our study smaller or not evident dysregulation of cytokines by donkey infected PBMC and macrophages may indicate that the pathogenesis of EIA in donkeys occur by different mechanisms from those established for the equine species. It indicates the need of more studies at donkey cellular immune response against EIAV, searching for other host factors, such as equine lentivirus receptor (ELR) and retroviral restriction factors (RRF).